Clinical Prognostic Factors in Pediatric Patients With Orthostatic Intolerance - Kazue Ishitsuka MD, MPH, PhD; Kaori Yamawaki MD; Miwako Horikawa MD; Hisaya Nakadate MD, PhD; Akira Nagai MD, PhD; Akira Ishiguro MD, PhD (SAGE Publishing, 2020)
Midodrine is widely used for orthostatic intolerance (OI); however, little is known about the prognostic factors of OI after midodrine treatment. We retrospectively reviewed electronic medical charts to investigate clinical prognostic factors of OI on 159 OI patients aged 7 to 18 years who were treated with midodrine at a children's hospital. Logistic regression was conducted to clarify predictors for improving symptoms at the first month of the treatment. Patients with orthostatic uncomfortable feeling or fainting were significantly more likely to improve symptoms at the first month of the treatment (odds ratio [OR], 3.48; 95% confidence interval [95%CI], 1.36-8.89), but patients with underweight were significantly less likely to improve symptoms (OR, 0.19; 95%CI, 0.06-0.56). Our results suggest that predictive factors for OI by midodrine treatments are orthostatic symptoms and underweight in pediatric patients. These findings are useful to develop further studies for OI treatments.